Production of Denatured Whey Protein Concentrate at Various pHfrom Wastewater of Cheese Industry - Robi Andoyo; Anindya Rahmana Fitri; Ratih Siswanina Putri; Efri Mardawati; Bambang Nurhadi; Nandi Sukri; Rudi Saprudin Darwis (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2021)
Wastewater produced from cheese industry is rich in biological component such as whey protein, fat and lactose. Whey protein is the residual liquid of cheese making process with a high protein efficiency ratio. The wastewater source used in this study was whey liquid from cheese processing industry located at West Java, Indonesia. Conversion of soluble whey protein into whey protein microparticle is required to produce food with nutritional value that can be adjusted to the needs of the specific target with high digestibility and palatability. Whey protein was collected by separation technique through heat treatment at specific condition. This was done by changing the heat treatment condition and pH of the samples. Changing the pH of the samples before heat treatment affect the ionic strength of the whey protein hence, altering the properties of the concentrate. This study aims to produce whey protein concentrate heated at various pH level and to observe physicochemical and functional properties of the concentrates. The method used in this research was a descriptive method conducted on three treatments and two replications namely whey protein concentrate production in a pH condition 6.4; 6.65; and 7.0. The parameters observed were physicochemical and functional properties. Furthermore, the result showed that there were decrease in protein content, along with the increasing pH before heat treatment. Microstructure image (SEM) showed a finer particles with the increasing pH. Meanwhile, solubility of the rehydrated samples tends to increase along with the increasing pH. The measurement of functional properties of the samples showed that denatured whey protein produced at different pH before heat treatment have different water holding capacity and a tendency to form bonds between protein particles thereby increasing the viscosity value. These physicochemical and functional properties were suitable for denatured whey protein to be used as a texture controller in whey protein based-food production.